Kelayakan Modul Sub Materi Konsep Keanekaragaman Hayati Dari Hasil Inventarisasi Pisang Di Desa Tanjung Saleh Kabupaten Kubu Raya - Kasmita Sari; Kurnia Ningsih; Anisyah Yuniarti (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
One of the uses of biodiversity is an inventory of bananas in Tanjung Saleh Village, Kubu Raya Regency, which is included in the module teaching materials including a concise, structured description, so that it is easy to understand and it is hoped that students will be able to involve themselves in achieving improvements in banana varieties in the future. The aim of this research is to determine the feasibility of the sub-material module of the biodiversity concept based on the results of a banana inventory in Tanjung Saleh Village, Kuburaya Regency, West Kalimantan. The research method used is a qualitative descriptive method with the data collection instrument used is validation of the product to be developed. Data analysis techniques are a method used to systematically compile data obtained from the results of instruments given to validators and students. Validation data were analyzed using Content Validity Ratio (CVR) analysis. The five aspects that were validated were appropriateness of content, language, presentation, graphics and effectiveness. Of the five aspects, there are seventeen criteria that are assessed to test the suitability of the module so that it can be seen whether the module is suitable or not suitable for use as teaching material in the learning process at school. The research results show that the module feasibility validation results of 0.99 are declared feasible, so the module can be used as teaching material in the biodiversity concept sub-material for class X SMA/MA.